2022
DOI: 10.3390/ma15249058
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Infrared Photoelectric Detection Performance of Pbs Quantum Dots through Solid-State Ligand Exchange

Abstract: Lead sulfide (PbS) quantum dots (QDs) have attracted a great deal of attention in recent decades, due to their value for applications in optoelectronic devices. However, optimizing the performance of optoelectronic devices through ligand engineering has become a major challenge, as the surfactants that surround quantum dots impede the transport of electrons. In this paper, we prepared PbS QD films and photoconductive devices with four different ligands: 1,2-ethylenedithiol (EDT), tetrabutylammonium iodide (TBA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 43 publications
0
5
1
Order By: Relevance
“…The TBAI enables the I – ions to further replace the long-chain ligand (OA – ) and then the EDT is employed to passivate the surface defects of the quantum dots. In contrast to our earlier results, we achieved excellent device performance based on the two-step treatment of the hybrid photodetector . It is shown that the improved passivation together with slower voltage decay indicates fewer surface trap states and less carrier recombination.…”
Section: Introductioncontrasting
confidence: 94%
See 3 more Smart Citations
“…The TBAI enables the I – ions to further replace the long-chain ligand (OA – ) and then the EDT is employed to passivate the surface defects of the quantum dots. In contrast to our earlier results, we achieved excellent device performance based on the two-step treatment of the hybrid photodetector . It is shown that the improved passivation together with slower voltage decay indicates fewer surface trap states and less carrier recombination.…”
Section: Introductioncontrasting
confidence: 94%
“…This is attributed to the increased capacity for charge carrier transport, a narrower gap between QDs, and a reduction in surface defects on QDs, which contribute to higher binding energy. 29 On the other hand, the EDT has a good surface passivation effect, thus reducing the defect density on the surface of the QDs induced by exposed hanging bonds (Figure S5). 39 QDs continued to be treated with the EDT(MAI/TBAI/EDT QDs), MAI/TBAI/EDT QDs have significant electrical properties.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The optical properties required for SCAPS software calculations are the optical absorption coefficients, which are obtained from the SCAPS absorption file database for ZnO shown in figure 2. (d), and from synthesis and testing in our laboratory [29,30] for PbS quantum dots. The quantum dots synthesized by the sol-gel method at 150  C were dissolved in toluene to form a 0.3 mg ml −1 solution, and the absorbance of solution A( ) l was tested under an ultraviolet (UV) spectrophotometer to obtain the absorption coefficient ( ) a l of the quantum dots, which was then normalized such that ( ) a l at the first exciton absorption peak was equal to the absorption coefficient value for bulk PbS film at this wavelength [31,32].…”
Section: Numerical Methodology and Device Structurementioning
confidence: 99%